Hakikat dan Nestapa Manusia Modern Perspektif Jalaluddin Rumi - Prayogo, Prasetyo (Jurnal Riset Agama, 2022)
Some hypotheses about the nature of man that have been shaped by various experts have reflected man's understanding of himself. Nevertheless, this understanding of human nature has not yet reached its final (final) point. The understanding of human nature is still developing today, so that an understanding of human nature can improve or perfect human science throughout intellectual history. Using philosophical and sufistic approaches or Islamic mysticism, this article will illustrate the idea of human nature according to jalaluddin Rumi's unusual view. The purpose of this study is to understand and analyze the nature of human beings simply in the sufistic teachings of Jalaluddin Rumi. The decision to choose Jalaluddin Rumi's sufistic approach as the object of study to understand the nature of man was caused by the human condition that had brought himself to lose the eschatologically lost meaning and motivation behind his own life. This research includes qualitative research using a library research approach to several primary and secondary literature. The results of this study show that the true nature of man lies in the part of his spirit (soul). The crisis that occurs in modern man today is a spiritual drought that has lost its true essence as a man created by God. For this reason, this study concludes that man must strive to trace his own spiritual essence, in order to always be a human being who is appointed by Allah Swt.